Warm Glow or Extra Charge? The Ambivalent Effect of Corporate Social Responsibility Activities on Customers’ Perceived Price Fairness - Habel, Johannes; Schons, Laura Marie; Alavi, Sascha; Wieseke, Jan (Journal of Marketing, 2016)
Prior research has firmly established that consumers draw benefits from a firm's engagement in corporate social responsibility (CSR), especially the feeling of a “warm glow.” These benefits positively affect several desirable outcomes, such as willingness to pay and customer loyalty. The authors propose that consumers do not blindly perceive benefits from a firm's CSR engagement but tend to suspect that a firm's prices include a markup to finance the CSR engagement. Taking customers’ benefit perceptions and price markup inferences into account, the authors suggest that CSR engagement has mixed effects on consumers’ evaluation of price fairness and, thus, on subsequent outcomes such as customer loyalty. The authors conduct one qualitative study and four quantitative studies leveraging longitudinal field and experimental data from more than 4,000 customers and show that customers indeed infer CSR price markups, entailing mixed effects of firms’ CSR engagement on price fairness. The authors find that perception critically depends on customers’ CSR attributions, and they explore the underlying psychological mechanisms. They propose communication strategies to optimize the effect of CSR engagement on perceived price fairness.